Pola Asuh Orang Tua Terhadap Kejadian Stunting Pada Balita Usia 24-59 Bulan - Wati, Ika Fujica; Sanjaya, Riona (Wellness And Healthy Magazine, 2021)
The prevalence of stunting in Indonesia is the second-highest after Cambodia in the Southeast Asian region.  Stunting is caused by multi-dimensional factors, one of which is poor parenting practices or parenting patterns.  The purpose of this study was to determine the relationship between parenting patterns and the incidence of stunting in toddlers aged 24-59 months. The design in this study was cross-sectional.  The population in this study were all parents of toddlers aged 24-59 months in the Neglasari village, the working area of the Tanjung Agung Health Center, South Lampung Regency as many as 117 people.  With a total sample of 100 mothers under five and the sampling technique was simple random sampling.  Processing data with SPSS 25 application with analysis test using Chi-Square test. The results showed that the majority of parenting patterns were good (74%) and the nutritional status of the majority of toddlers was not stunted, then the test results showed that there was a significant relationship between parenting parents on the incidence of stunting in toddlers aged 24-59 months in the village of Neglasari, the work area of the Tanjung Agung Health Center, South Lampung Regency in 2021 with a p-value of 0.000 less than 0.05.  Advice is given to health workers to be able to intervene to reduce stunting, especially counselling about the importance of parenting Abstrak: Prevalensi stunting di Indonesia berada di peringkat kedua tertinggi setelah Kamboja di kawasan Asia Tenggara. Stunting disebabkan oleh faktor multi dimensi, salah satunya adalah praktek pengasuhan atau pola asuh orang tua yang kurang baik. Tujuan penelitian ini untuk mengetahui hubungan pola asuh orang tua terhadap kejadian stunting pada balita usia 24-59 bulan  Desain dalam penelitian ini adalah cross sectional. Populasi dalam penelitian  ini adalah seluruh orang tua balita usia 24-59 bulan yang ada di desa Neglasari wilayah kerja Puskesmas Tanjung Agung Kabupaten Lampung Selatan sebanyak 117 orang. Dengan jumlah sampel sebanyak 100 ibu balita dan Teknik pengambilan sampel dengan simple random sampling. Pengolahan data dengan aplikasi SPSS 25 dengan Uji analisis menggunakan uji Chi Square.Hasil penelitian menunjukkan bahwa mayoritas pola asuh orang tua adalah baik (74%) dan status gizi pada balita mayoritas tidak stunting, kemudian hasil uji menunjukkan bahwa ada hubungan yang signifikan antara pola asuh orang tua terhadap kejadian stunting pada balita usia 24-59 bulan  di desa Neglasari wilayah kerja Puskesmas Tanjung Agung Kabupaten Lampung Selatan tahun 2021 dengan  nilai p value 0,000 kurang dari 0,05. Saran yang diberikan kepada tenaga kesehatan untuk dapat melakukan intervensi penurunan stunting terutama penyuluhan tentang pentingnya pola asuh orang tua